2016
DOI: 10.1111/aos.13080
|View full text |Cite
|
Sign up to set email alerts
|

In vivo biometric evaluation of Schlemm's canal with spectral‐domain optical coherence tomography in pseuduexfoliation glaucoma

Abstract: Anterior segment spectral-domain optical coherence tomography offers non-invasive, in vivo measurement of the SC, and it could be used for investigating the SC changes in patients with PEX glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…ird, exfoliation may promote scar formation in the filtering area. Iris angiopathy and destruction of the blood-aqueous barrier can cause postoperative cellulose-like exudation, and neovascularization of the iris can cause intraoperative or postoperative hyphema [19,20]. In this study, one case of hyphema was found after PXG surgery.…”
Section: Discussionmentioning
confidence: 54%
“…ird, exfoliation may promote scar formation in the filtering area. Iris angiopathy and destruction of the blood-aqueous barrier can cause postoperative cellulose-like exudation, and neovascularization of the iris can cause intraoperative or postoperative hyphema [19,20]. In this study, one case of hyphema was found after PXG surgery.…”
Section: Discussionmentioning
confidence: 54%
“…() reported larger SC cross‐sectional areas (13 991 ± 1357 μ m 2 ) for healthy Chinese adults, while Imamoglu et al. () described smaller values of 5000 μ m 2 measured by OCT in healthy Turkish adults. The possibility that, besides the measurement method, ethnicity could explain some of the differences observed needs to be explored.…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, Imamoglu et al. () found that both SC length and area did not correlate with factors such as axial length and anterior chamber depth. However, we did detect a significant link, although with a mild correlation, between SC diameter and age.…”
Section: Discussionmentioning
confidence: 98%
“…17,18 Researchers have used OCT to investigate properties of SC in vivo in mice and humans. 17,[19][20][21][22][23][24][25][26] These studies were limited in axial resolution (2-5 μm) and field of view (0.5-3 mm). Imaging the detailed structure of SC in mice requires overcoming several hurdles.…”
mentioning
confidence: 99%